Dopamine Signaling in Dorsal Versus Ventral Striatum: The Dynamic Role of Cholinergic Interneurons - Threlfell, Sarah; Cragg, Stephanie J. (Frontiers in Systems Neuroscience, 2011)
Mesostriatal dopaminergic neurons and striatal cholinergic interneurons participate in signalling the motivational significance of environmental stimuli and regulate striatal plasticity. Dopamine (DA) and acetylcholine (ACh) have potent interactions within the striatum at multiple levels that include presynaptic regulation of neurotransmitter release and postsynaptic effects in target cells (including ACh neurons). These interactions may be highly variable given the dynamic changes in the firing activities of parent DA and ACh neurons. Here, we consider how striatal ACh released from cholinergic interneurons acting at both nicotinic and muscarinic ACh receptors powerfully modulates DA transmission. This ACh-DA interaction varies in a manner that depends on the frequency of presynaptic activation, and will thus strongly influence how DA synapses convey discrete changes in DA neuron activity that are known to signal events of motivational salience. Furthermore, this ACh modulation of DA transmission within striatum occurs via different profiles of nicotinic and muscarinic receptors in caudate-putamen compared to nucleus accumbens, which may ultimately enable region-specific targeting of striatal function.